Vitrimer-like of poly (glycerol sebacate) by using zinc acetate, zinc oxide and Amberlyst as catalysts - Thongkam, Montree; Saowsupa, Sairoong; Rungrojchaipon, Pesak (My University, 2023)
Polyglycerol sebacate (PGS) is elastomeric biodegradable polymer with potential biomedical and green packaging applications. This study focuses on the synthesis of vitrimer-like PGS utilizing various catalysts, including Zinc acetate, Zinc oxide and Amberlyst-15. The investigation of vitrimer-like of PGS polymer by polycondensation of glycerol and sebacic acid with various molar ratio of 1:1, 1:1.25 and 1:1.5 will be studied. The synthetic time and temperature were controlled at 72 h, 120 °C, respectively. The prepolymer of PGS had a weight-average molecular weight (Mw.) of 1743. The result of functional group was confirmed by Fourier transforms Infrared spectroscopy (FTIR). The intense C[dbnd]O stretch at 1737 cm−1 confirms the formation of ester bonds. The intense OH stretch at 3454 cm−1 indicated hydroxyl groups from hydrogen bonded. When the quantity of catalyst is increased, the results of hardness are rising but swelling (%) becomes lower. The results showed a polymer network has higher cross-link when the catalyst increases. In addition, the proton nuclear magnetic resonance spectroscopy (1H NMR) analysis found that PGS using catalyst does not have peaks of glycerol.
Keywords: Biodegradable polymer; Glycerol; Poly (glycerol sebacate); Sebacic acid